MANAJEMEN STRATEGIK POSYANDU DALAM UPAYA PENANGGULANGAN STUNTING (STUDI KASUS POSYANDU WIJAYA DAN KEMUNING KELURAHAN PURWANEGARA, KECAMATAN PURWOKERTO UTARA) - Chanifia Izza Millata; Chamid Sutikno (Economics, Social, and Humanities Journal (Esochum), 2023)
This study aims to understand how the strategic management of Posyandu Wijaya and Kemuning in Purwanegara Village, Purwokerto Utara District, Banyumas Regency in efforts to tackle stunting. This research uses descriptive qualitative method. This study uses the theory of SWOT analysis. Based on this theory, it can be found that Posyandu Wijaya and Kemuning have four factors, namely Strength, Weakness, Opportunity, and Threat. Posyandu's strength is seen as the closest health service organization to the community, especially toddlers and pregnant women. Weaknesses that exist come from the lack of capacity of cadres, toddlers who are afraid of posyandu, and the lack of knowledge of parents about the importance of posyandu. Opportunity can be seen from the existence of support for posyandu from the sub-district, health center, or other institutions. Meanwhile, threats can be seen from the Covid-19 pandemic which forced the Wijaya and Kemuning Posyandu to stop their activities, the lack of support from some people, and the threat of hoaxes through social media.